Midnight school 3d game design - Nabilla Nurhaliza; Apriansyah (Yayasan Pendidikan Rafisqy Arfadhia, 2022)
The game that is a favorite among gamers is the FPS type game ( First Game).Person Shooter ) and the horror genre. This research designs game genre horror and FPS type which is a very interesting combination for developed. The author will develop this game using Blender software as an in- game terrain creation, programming language C# and uses Unity 3D 5.3 as its engine. The features of this game are:mysteries/riddles, hints, and jumpscares where players will be surprised with sound, moving objects and so on. Device design method The software used is the Extreme Programming (XP) Development Method. which has the following stages: Planning, Design, Coding and Testing. The results of the research are in the form of a game called Midnight School with see First Person Shooter Horror 3D setting. Ease of Rating the game can be concluded based on the opinion of the respondents as a whole ie this game is very easy to play.